A Regional Company? RED Production and the Cultural Politics of Place. Issue 3 (July 2019) - Spicer, Andrew
Abstract : This article explores the significance of RED Production's location in the north-west of England, analysing the complexities of its positioning as a 'regional' company contextualised within the broader issues surrounding regional television production created by the politics and regulation of UK broadcasting. The article contends that recent analyses of creative clusters have privileged economic factors over cultural ones and provides a counter argument that demonstrates the importance of historical evolution and cultural traditions in understanding why RED has been so successful. It examines the significance of an anti-metropolitan discourse of northernness as a broad cultural tradition that shapes RED's identity and production strategy, and, more specifically, the profound legacy of the Manchester-based Granada Television. The article explores the reasons for and consequences of RED's move to MediaCityUK in 2013 and its acquisition by the European conglomerate Studiocanal. It also discusses the ongoing problem of the vexed relationship between London and the regions in British broadcasting, and the impact of an increasingly international orientation on how television production companies position themselves in a changing marketplace.